The Diagnostic Utility of p16 Immunostaining in Differentiating Cancer and HSIL from LSIL and Benign in Cervical Cells. Issue 2 (February 2019) - Wu, Ming-Zhe; Wang, Shiyu; Zheng, Min; Tian, Li-Xiang; Wu, Xin; Guo, Ke-Jun; Zhang, YI; Wu, Guang-Ping
Cervical liquid-based cytology plays an important role in the diagnosis of cervical squamous intraepithelial lesion (SIL). However, cytological evaluation alone has a relatively low sensitive. To overcome this problem, HPV DNA testing or HPV DNA combined with cytology has been applied. HPV DNA testing significantly improved the sensitivity, but the specificity is low, especially in cancer and high-grade SIL (HSIL) cases. The aim of this study was to evaluate the diagnostic utility of p16 overexpression in cervical cells of patients with HSIL and cancer. The expression of p16 was detected by immunostaining in liquid-based cells from cervical brushing in 278 patients which including: Cancer ( n = 13), HSIL ( n = 112), low-grade SIL (LSIL) ( n = 45), and Benign ( n = 108). The expression levels of p16 were significantly higher in the cancer and HSIL groups when compared with the LSIL and Benign groups ( P < 0.01). The accurate diagnostic rates of cancer and HSIL were significantly increased by p16 immunostaining plus cytology than that by cytology alone ( P < 0.01). The false negative or false positive of p16 immunostaining occurred with a unicellular pattern. With sensitivity of 96.0% and accuracy of 91.7%, the diagnostic performance of p16 immunostaining was much better than that of cytology alone with sensitivity of 36.0% and accuracy of 70.9% ( P < 0.01). p16 immunostaining in cervical brushing cells may not only be used as an ancillary tool to cytological diagnosis of cervical neoplasia but also help to distinguish HSIL from LSIL and the triage of transient infection.